The Regulation of Third Party Campaigning in UK Elections. Issue 4 (17th August 2020) - Rowbottom, Jacob
Abstract: This article looks at the regulation of third parties in UK election law. During the 2019 general election campaign, media reports noted an increase in non‐party organisations spending money on electoral advertisements on social media. Such advertisements raised a number of ethical questions, related to spending, transparency, and the content of the messages. Despite such recent concerns, third party electoral activity in the UK is not new, and the existing legal framework regulates campaign spending. That framework has its roots in Victorian‐era election law and has been periodically updated. This article will look at the challenges in designing laws to regulate third party electoral activity, as a difficult line has to be drawn to ensure the laws are effective, while at the same time not imposing too many burdens on independent political activity. Moreover, the move to digital campaigning poses some further challenges, such as monitoring compliance by third party campaigners. While there are no simple solutions to some of the issues raised by third party electoral activity, this article will note some of the measures that could at least improve the transparency of such campaigning.